Pengaruh Kualitas Produk Dan Harga Terhadap Loyalitas Pelanggan Pada Toko Rumah Jahit Akhwat Makassar - Akbar Akbar; Nurhaedah Nurhaedah (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
The purpose of the study was to determine the effect of product quality and price on customer loyalty at the Akhwat Makassar sewing house shop (Comparative Study at the RJA Store, Perintis and Alauddin branches). , obtained from the questionnaire. The population of this study was 100 consumers of the Akhwat Sewing House of the Perintis branch and Alauddin Makassar. The sampling in this study used the slovin method with the calculation results were 50 respondents. The analysis of this research is Multiple Linear Regression. This analysis is used to determine how much influence the independent variables, namely product quality and price (X1 and X2), have on these variables, namely customer loyalty (Y). The results showed that product quality had a positive and insignificant effect on customer loyalty at the RJA Makassar Store. Price has a positive and significant effect on customer loyalty at the RJA Makassar Store. Product quality and price have a positive and significant effect on customer loyalty at the RJA Makassar Store with a large influence of 69.10%.